Oxygen catalyst depletion strategy based on TWC control-oriented modelling⁎. Issue 31 (2018) - María Desantes, José; Guardiola, Carlos; Pla, Benjamín; Real, Marcelo
Abstract: This paper presents and experimentally evaluates different model-based O2 depletion strategies for the TWC during a tip-in after a fuel cut-off. The objective is to find an optimal depletion strategy in the sense of minimum fuel consumption while keeping NOx emissions during the transient below certain limit. To do that, in the present paper, a control oriented model of the TWC is combined with a Direct Method to solve the corresponding Optimal Control Problem. The analysis of the obtained results allows to design model-based control strategies whose performance is experimentally assessed. In particular, the results obtained show the tradeoff between fuel consumption and NOx emissions during the analysed transient.